GENETIC ASPECTS OF THE COMMERCIALLY USED SEA URCHIN Tripneustes gratilla - Abdul Hamid A. Toha; Robi Binur; Suhaemi Suhaemi; Lutfi Lutfi; Luchman Hakim; Nashi Widodo; Sutiman B. Sumitro (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2014)
Tripneustes gratilla is economically important, supports small-scale, commercially important, ecological values, a prospect as a biological control agent and also considered as the commercially traded sea urchin. We review genetic aspects of T. gratilla for understanding the status to the sustainable use in the future. In GenBank, there are 267 nucleotide sequences related with T. gratilla. Most of the sequences (189 sequences) are COI gene of T. gratilla from Indo-Pacific Ocean. Study on molecular genetics mentioned that there is no genetic structure for T. gratilla distribution in Indo-Pacific Ocean including in Indonesia waters.